Media, politics, and hate speech: a critical discourse analysis / Adisa Rasaq ... [et al.] - Rasaq, Adisa; Udende, Patrick; Ibrahim, Abubakar; Oba, La'aro (2017)
The effects of political activities in developing countries and particularly Nigeria have shown that hate speech has become more vivid in the successive democratic dispensation than the previous ones thereby keeping the citizens more divided. Though, on the issue of hate speech the provisions of Nigeria Constitution, Nigeria Electoral Act and Journalism Ethic Code are clear but the question is where to draw the line between political statement, hate speech and the responsibility of the media. Therefore, this research sought to establish through a Critical Discourse Analysis approach the pervading of hate speech in Nigeria particularly in Nigeria's 2015 general election which has become possible helix of violence. Based on the discourse, it is clear that hate speech was the focal point and the instrument of campaign. Therefore, the parade of hate speeches in several newspapers analyzed showed that media was used by politicians to stoke up hatred and stimulate violence among ethnic and political groups during the electioneering periods as well as in the daily life. Hence, it is recommended that media outfits should always examine politicians' messages and evaluate their words, scrutinize their facts and claims, and judge carefully the intention and likely impact on the society to prevent being an accomplice in hate speech.